An exploration of mechanical engineering students' perceptions of the influence of their work placement experiences on their employability - Ngonda, Tiyamike Nyozani (Department of Mechanical Engineering, 2021)
Most researchers agree that work placement has a positive influence on students' employability. Despite this consensus, there has been conflicting research on the factors that contribute to this influence. Moreover, the social mechanisms through which this outcome is realised have not been well understood. To address these shortcomings, this study explores how mechanical engineering students' work placement experiences facilitate or hinder the growth of their occupational competency and self-efficacy, two commonly used indicators of student employability. It provides a clear explanation of the factors and social mechanisms that produce employability outcomes and it is hoped that this would enable the implementation of work placement programs in a manner that would promote rather than hinder students' employability. The study is informed by social cognitive theory's triadic reciprocal causation model, which suggests that student learning arises from interactions of environmental, personal, and behavioral factors. It is further informed by situated cognition, a sociocultural theory that focuses on learning through participation. The study collected qualitative data from a sample of 34 mechanical engineering students from a South African university of technology who were undergoing a year-long work placement. Data were collected using semi-structured interviews as well as document analysis of the students' logbooks and evidence portfolios. Thereafter, a two-phase qualitative analysis comprising thematic analysis and thematic synthesis was conducted. The thematic analysis produced seven themes: the learning environment, the industry mentor, student performance and participation as learning, quality of work affordances, student characteristics, student's agentic role and student learning trajectory. These themes represented elements of students' work placement experiences that they considered influential in the growth of their occupational competency and self-efficacy. The thematic synthesis uncovered work placement as a system with emergent outcomes arising from interactions of its variables. These interactions were represented by a qualitative systems dynamics model with negative and positive reinforcing loops. An enabling reinforcing feedback loop explained the growth of the students' occupational competency and self-efficacy, and a constraining reinforcing feedback loop explained how such growth was hindered. This qualitative systems dynamics model may resolve previous studies' explanatory shortcomings by illuminating the processes through which work placements' occupational outcomes are realised.